SOSIALISASI DAN PENDAMPINGAN SERTIFIKASI PRODUK HALAL DESA DUKUHDIMORO - Novia Ayu Sekar Pertiwi; Indy Asna Azizah; Mega Mustika; Nur Abibah; Rahmat Maulana Sukma Dewantara; Anis Fauziyah (Institute for Research and Community Services, 2024)
Halal certification on a product nowadays has become a necessity. Because society will be more selective and products that do not have halal certification will be abandoned. Based on the results of interviews with several Micro, Small and Medium Enterprises (MSMEs) in Dukuhdimoro village, especially the food sector, they do not yet have halal product certification, because many business actors in Dukuhdimoro Village have not registered their businesses for halal certification, Lack of dissemination of information about the requirement for halal certification so that there are several business actors who do not know about halal certification, Business actors in Dukuhdimoro Village do not understand the importance of products with halal certification, Business actors in Dukuhdimoro Village still do not know well how to register halal certification for their products and postpone registering it, and Business actors in Dukuhdimoro Village still think that the halal certification process is complicated. The solution to these problems includes socialization and assistance for halal product certification. MSME actors, especially in the food and beverage sector, are given information and assistance regarding halal certification registration. After the socialization and assistance of halal certification of MSME products, business actors, especially food and beverage businesses in Dukuhdimoro Village, understand the importance of products with halal certificates and how to register their products. The final result of this socialization and assistance of halal certification, these business actors registered their businesses to obtain halal certificates.